Leveraging the translational science benefits model to enhance planning and evaluation of impact in CTSA hub-supported research - Andrea Molzhon; Pamela M. Dillon; Deborah DiazGranados; Deborah DiazGranados (Frontiers in Public Health)
IntroductionIncreasingly, the public, policymakers, and funders expect clinical research to show tangible effects on public health. However, assessing research impact is challenging. Most researchers are not trained to consider the broad-ranging impacts of their work. The TSBM is a conceptual framework that includes four domains of impact: clinical, community, economic, and policy. We assess the utility and acceptability of using a survey based on the TSBM as a means to help researchers identify their potential research impacts.MethodsCTSA program-supported investigators self-reported the potential benefits of their research projects in an electronic survey based on the TSBM. Responses were reviewed and scored by program evaluators. Survey acceptability was measured by response and completion rates; utility was measured by comparing benefits identified in the survey but not described in the researcher’s grant application; and quality was measured by the degree of congruence between investigators’ responses and evaluators’ determinations regarding the potential benefits of the research.ResultsOf the investigators invited to participate, 67% completed the survey. Half of the investigators identified at least one benefit from their research not described in their research proposals. The rate of agreement across all responses between the investigators and the evaluators was 60%.DiscussionOur study showed that a survey based on the framework of the TSBM was an acceptable and useful tool to help investigators identify research impact. However, our work also suggested that there are opportunities to educate investigators especially about the long-term, broad-reaching effects of their work. Ultimately, this work may help researchers conceptualize and realize the public health impact of their research.